Perancangan Tampilan Antarmuka Aplikasi Olahrga Otodidak "Skillzone" dengan Metode Design Thinking - Prawira, Revan Aditya; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 3 (2025): JNATIA Vol. 3, No. 3, Mei 2025DO - 10.24843/JNATIA.2025.v03.i03.p16, 2025)
In communities that are busy with high activity and mobility, the time spent keeping healthy and fitness is often limited. Limited access to facilities makes for a roadblock. This research offers a solutive strategy by using mobile applications to plan sports according to daily user routines. The focus of research is the development of user interfaces and user experiences mobile applications aimed at overcoming lack of knowledge and fitness support. Using the Design Thinking method, the research identified the user's main difficulties in managing time and maintaining consistency in exercise. From a survey of 15 respondents with 15 - 25 years old age range, the application scored 80.5 (grade B) with a System Usability Scale method . W ith a Design Thinking method, the Skillzone can identify user challenges and devise solutions that suit their needs .